ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA ANGIN DI TAMAN TEKNOLOGI TOWER TURYAPADA - Muhabil, Ihsan; Hari, Krisna; Hasan, Ismail; Oka Widyantara, I Made; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUM, 2024)
Tower Turyapada is a technology concept tourism center with various attractions located in Pegayaman Hill, Singaraja and is programmed to meet Building Green Building (BGH) criteria. One component of the BGH assessment is the use of renewable energy. The use of renewable energy that is suitable to be utilized in this tower building is PLTB (Wind Power Plant), because it is located in a hilly area with strong winds. The potential of wind power plant has been analyzed using descriptive method through quantitative approach. Analysis of wind energy potential using primary data by taking direct measurements in the Turyapada Tower area in February - March and using secondary data from the I Gusti Ngurah Rai Meteorological Station, Badung Regency. The analysis results show the average value of wind speed in the Tower Turyapada area in February - March amounted to 3.55 m / s and 4.58 m / s. The wind turbine specification uses TSD-500. Wind turbine specifications use TSD-500 because it can generate electricity at low wind speeds and uses 10 units of turbines. The results of the analysis obtained electrical energy of 2,159 kWh / year. The electrical load requirement of the Pedestal Building as the main building of the Turyapada Tower Technology Park is 7,787,000 kWh / year, so it cannot meet the electrical load of the Pedestal Building because it only supplies power by 0.00028%. This research was conducted to find out how much wind energy can produce electrical energy with wind energy conditions in the Turyapada Tower Area.